Effect of Synthesis Methods on the Characteristics of Fe₃O₄/rGO Nanocomposites and Their Potential for Electrochemical Sensing: A Systematic Review - Indrawan Eka Badri; Kormil Saputra; Dian Wijaya Kurniawidi; Ishmah Luthfiyah (Tinta Emas Publisher, 2026)
Fe3O4/rGO nanocomposites have attracted considerable attention for electrochemical sensing because they combine the high electrical conductivity and large surface area of reduced graphene oxide (rGO) with the magnetic and electrocatalytic properties of Fe₃O₄. This systematic review aims to evaluate recent advances in Fe3O4/rGO nanocomposites published between 2021 and 2026, with particular emphasis on the relationships among synthesis methods, material characteristics, and electrochemical sensing performance. The review was conducted following the PRISMA 2020 guidelines using Scopus, PubMed, and ScienceDirect databases. After systematic screening based on predefined inclusion and exclusion criteria, five eligible experimental studies were included in the qualitative analysis. The findings demonstrate that synthesis parameters strongly influence the morphology, crystallinity, interfacial interactions, and electrochemical properties of Fe3O4/rGO nanocomposites. Hydrothermal and solvothermal methods generally produce more homogeneous and crystalline structures, whereas green synthesis and waste-derived precursors offer environmentally sustainable alternatives. Furthermore, multi-component systems incorporating conductive nanomaterials or polymers exhibit enhanced sensing performance through improved electron transfer and larger electroactive surface areas. Overall, Fe3O4/rGO nanocomposites represent a promising platform for electrochemical sensors and biosensors. Future research should focus on synthesis standardization, comprehensive material characterization, reproducibility, and sustainable fabrication strategies to accelerate practical sensor development.